2009
DOI: 10.3892/or_00000666
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NADH-dehydrogenase polymorphisms as sporadic breast cancer risk factor

Abstract: Abstract. Breast cancer is the most frequently diagnosed female cancer all over the world. Although the molecular genetics of this disease has been the focus of many projects for over 20 years, the number of prognostic markers used in clinics is still unsatisfactory. Mitochondrial DNA mutations have been reported in many breast cancer studies. To investigate the possible role of mitochondrial inherited polymorphisms in breast cancer development we analyzed the sequence of NADH-dehydrogenase genes in cancer sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Given the results of studies on other diseases associated with mtDNA variations, according to Mao et al, 33 variations in the MT‐ATP6 and MT‐CYB genes might play a role in the unexpected fertilization disorder. The A8860G mutation in the ATPase‐6 gene was detected in 79%−91.66% in breast tumors, 75%−100% in other types of cancers 32,33 and 92.85%−100% in neurodegenerative diseases 34,35 . In the present study, 32 COVID‐19 (+) patients had A8860G missense mutation in the ATPase‐6 gene.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Given the results of studies on other diseases associated with mtDNA variations, according to Mao et al, 33 variations in the MT‐ATP6 and MT‐CYB genes might play a role in the unexpected fertilization disorder. The A8860G mutation in the ATPase‐6 gene was detected in 79%−91.66% in breast tumors, 75%−100% in other types of cancers 32,33 and 92.85%−100% in neurodegenerative diseases 34,35 . In the present study, 32 COVID‐19 (+) patients had A8860G missense mutation in the ATPase‐6 gene.…”
Section: Discussionsupporting
confidence: 46%
“…The A8860G mutation in the ATPase-6 gene was detected in 79%−91.66% in breast tumors, 75%−100% in other types of cancers 32,33 and 92.85%−100% in neurodegenerative diseases. 34,35 In the present study, 32 COVID-19 (+) patients had A8860G missense mutation in the ATPase-6 gene.…”
Section: Discussionmentioning
confidence: 50%
“…We further annotated each variant for its associated disease phenotypes using MITOMAP 46 and observed that 10398A>G was associated with the largest number of distinct phenotypes of any reported MT variant (n=10). 10398A>G has been linked with AD 17 , Parkinson's disease [18][19][20][21][22][23][24] , breast cancer [25][26][27][28][29][30][31][32][33][34] , type 2 diabetes and many other diseases and conditions [35][36][37][38][39] .…”
Section: A>g Is Significantly Associated With Mitochondrial Heteroplasmymentioning
confidence: 99%
“…10398A>G corresponds to the Thr114Ala missense mutation of the MT-ND3 gene coded by the MT, and is a common variant found within most populations with a reported allele frequency of 41.8% from the gnomAD database v3.1.1 16 . The 10398A>G allele has been collectively associated with an expansive set of phenotypically diverse diseases including AD 17 , Parkinson's disease [18][19][20][21][22][23][24] , breast cancer [25][26][27][28][29][30][31][32][33][34] , gastric cancer, type 2 diabetes and several other human diseases and phenotypes [35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“… 1 The individual risk of breast cancer manifestation is contingent on a myriad of factors, encompassing age, gender, the presence of benign breast tumors, timing of menopause, hormone therapy, chest radiation exposure, combined use of estrogen and progesterone, alcohol consumption, diethylstilbestrol ingestion, genetic predisposition, postmenopausal obesity, age at first pregnancy exceeding 30 years, breastfeeding practices, and assorted environmental influences. 2 3 4 Breast cancer pathogenesis is intricately linked to genetic determinants, involving disruptions in gene expression levels, epigenetic alterations, and polymorphisms in DNA sequences. 5 Amidst the multifaceted array of environmental factors influencing cancer progression, vitamin D emerges as a significant modulator.…”
Section: Introductionmentioning
confidence: 99%